The pleiotropic effects of liraglutide in obesity-linked diseases - Kozdrowicki, Michał; Kaleta, Konrad; Kajtel, Aleksandra; Tekieli, Beata; Kęska, Mateusz; Lorkowska-Zawicka, Barbara; Bujak-Giżycka, Beata (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Obesity, defined by a BMI ≥30 kg/m², is a global epidemic associated with increased mortality rates and an increased prevalence of chronic diseases. Such diseases include type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), cardiovascular disease (CVD), and polycystic ovary syndrome (PCOS), besides several mental health disorders. Liraglutide, a glucagon-like peptide 1 (GLP-1) analogue, is widely recognized for its efficacy in glycemic control and weight loss and this review aims to explore the pleiotropic effects of liraglutide in obesity-related diseases. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Literature search was performed between 2022 and 2024 using the following databases: PubMed (MEDLINE) and Google Scholar. The comprehensive review of the literature focused on the action of liraglutide on NAFLD/ NASH, CVD, mental disorders, and PCOS. A qualitative synthesis of the data focusing on efficacy of liraglutide in obesity-related disease outcomes was performed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Liraglutide improves metabolic outcomes by promoting weight loss, reducing appetite, and improv ing glycemic control. In NAFLD/NASH, liraglutide reduces intrahepatic fat, liver fibrosis, and inflammation that strongly relate to the degree of weight loss. The LEADER trial showed its cardiovascular benefits in terms of reducing all-cause mortality and major cardiovascular events in patients with T2DM, although its chronotropic effects may pose risks in patients with heart fail ure. In women with PCOS, liraglutide reduces hyperandrogenism, insulin resistance, and body weight, and thus has even more favorable effects compared with metformin. Liraglutide also counteracts antipsychotic-induced weight gain and improves metabolic markers in patients with severe mental disorders. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Liraglutide demonstrates significant pleiotropic effects apart from weight reduction, including improved hepatic metabolism, cardiovascular protection, and better outcomes in PCOS and mental health. While semaglutide and tirzepatide may offer enhanced efficacy, liraglutide remains a promising therapeutic option for managing obesity and its related comor bidities.